Collagen degradation in ischaemic rat hearts. - Takahashi, S (1990)
Myocardial extracellular matrix is organized into a complex arrangement of intercellular and pericellular fibres and fibrils that serves as a supporting framework for contracting cells. Recent evidence suggests that changes in ventricular shape and function occurring after ischaemic injury may be related to alterations of this matrix. In this report we describe the rapid and extensive loss of collagen in myocardial infarction produced by ligating the left anterior descending coronary artery of the rat for 1-3 h. The total collagen content in the myocardial infarct zones after 1, 2 and 3 h of ligation was 75 +/- 8%, 65 +/- 7% and 50 +/- 10% respectively (mean +/- S.D.) of that of either the non-infarcted tissue controls or of the same regions in sex- and age-matched normal left ventricles. A marked decrease also occurred in the residual collagens which were not extractable with 6 M-guanidine hydrochloride, suggesting that rapid degradation of insoluble collagen fibres may also occur. The decreased collagen content in the 3 h myocardial infarct coincided with the appearance of several enzyme activities. Collagenase, other neutral proteinase and presumed lysosomal serine proteinase activities were increased by 3, 3 and 2 times the control values respectively. These results suggest that the increased activities of collagenase and other neutral proteinases may be responsible for the rapid degradation of extracellular matrix collagen in myocardial infarct.